Meneropong Konsepsi Negara Kesatuan dengan Sistem Otonomi Seluas-Luasnya - S. Endang Prasetyowati (KEADILAN PROGRESIF, 2011)
This study is about the implementation unitarty state with decentralization or autonomysystem. Autonomy as a principle of local governance based on the provisions ofarticle 18 of 1945 constitution and Local government law No.32 year 2004. Thisprovision states that Indonesia adopts a quasi-federal unitary state building, theUnitary Conception in Article 18 UUD 1945, the problem of residual power,institutional Parliament as the legislative.